"I'm not homeless, I'm houseless": identifying as homeless and associations with service utilization among Los Angeles homeless young people. Issue 1 (2nd January 2017) - Winetrobe, Hailey; Rhoades, Harmony; Rice, Eric; Milburn, Norweeta; Petering, Robin
ABSTRACT: Little is known about homeless young people's identification of being homeless and how that identity may or may not be associated with service utilization. This study of 444 homeless young people attending Los Angeles area drop-in centers explores the associations of demographic characteristics, homelessness characteristics, negative lifetime experiences, mental health symptoms, technology use, and past month service utilization with identifying as homeless. Fifty-two percent of the sample identified as being homeless. Being Black, a current traveler, and history of injection drug use were all significantly associated with a decreased likelihood in identifying as homeless. However, having fair/poor health, accessing shelter services, and reporting one's own substance use as a reason for homelessness were all significantly associated with identifying as homeless. There are important service implications for reaching young people who are in need of services but may not identify with the target population label of homeless.